Rapamycin Ameliorates Proteinuria and Restores Nephrin and Podocin Expression in Experimental Membranous Nephropathy - Stratakis, Stavros (Hindawi Publishing Corporation, 2013)
Objective. Recent studies have shown a beneficial effect of rapamycin in passive and active Heymann Nephritis (HN). However, the mechanisms underlying this beneficial effect have not been elucidated. Methods. Passive Heymann Nephritis (PHN) was induced by a single intravenous infusion of anti-Fx1 in 12 Sprague-Dawley male rats. One week later, six of these rats were commenced on daily treatment with subcutaneous rapamycin 0.5 mgr/kg (PHN-Rapa). The remaining six rats were used as the proteinuric control group (PHN) while six more rats without PHN were given the rapamycin solvent and served as the healthy control group (HC). All rats were sacrificed at the end of the 7th week. Results. Rapamycin significantly reduced proteinuria during the autologous phase of PHN. Histological lesions were markedly improved by rapamycin. Immunofluorescence revealed attenuated deposits of autologous alloantibodies in treated rats. Untreated rats showed decreased glomerular content of both nephrin and podocin whereas rapamycin restored their expression. Conclusions. Rapamycin monotherapy significantly improves proteinuria and histological lesions in experimental membranous nephropathy. This beneficial effect may be mediated by inhibition of the alloimmune response during the autologous phase of PHN and by restoration of the normal expression of the podocyte proteins nephrin and podocin.